Dental Caries in Diabetic Patients With Different Socioeconomic Status Using Mandibular First Molar as an Indicator (Bangladesh Journal of Infectious Diseases, 2026)
Background: The bacterial fermentation process of dietary carbohydrates is considered the main factor in developing dental caries, which is the most common chronic illness globally.Objective: The objective of this research was to evaluate the prevalence of dental caries in diabetic patients with different socioeconomic backgrounds using permanent mandibular first molar teeth as an indicator.Methodology: This cross-sectional research has a study group consisting of 90 randomly selected patients aged 17 to 75 years, 70 of them have diabetes. A non-invasive clinical dental examination was performed at the Dental Clinic of Al-Ameed University College of Dentistry. Statistical processing of the obtained research results was carried out in the environment of the IBM SPSS Statistics 23 application program.Results: Research data show a relationship between dental caries and socioeconomic status (p